Terahertz Generation Through Difference Frequency Mixing of Signal and Idler from an Optical Parametric Amplifier - Tigga,Celine Varence (Lund Reports on Atomic Physics (LRAP), 2025)
The thesis investigates the generation of terahertz (THz) radiation through difference-frequency generation (DFG) using chirped and unchirped near-infrared pulses. THz radiation enables the study of phonon dynamics in matter through direct interaction with the crystal lattice. THz radiation is used to induce low-energy excitations in matter while simultaneously avoiding large increases in sample temperature. Several methods exist that allow the generation of THz within a narrow band. Two optical pulses, close in frequency, produce an optical beat equal to their difference frequency. This field when incident on a nonlinear crystal generates difference frequencies with a narrow band. This forms the basis of the scheme implemented in the thesis project. The method for introducing chirp and delay in the scheme was studied only theoretically via simulations and was not implemented as a laboratory setup. An electro-optic sampling setup for characterizing the generated THz was planned but could not be completed within the time-frame of the project. A numerical model was developed using the symmetric split-step Fourier method (SSFM) combined with a fourth-order Runge–Kutta algorithm to simulate nonlinearpropagation of signal and idler fields inside a nonlinear crystal. Scaling techniques were introduced to maintain numerical stability, and the fields were recovered in physical units at the end of the simulations. Pulse energies at the input to the crystal were compared with the output THz pulse energy to obtain the value of THz conversion efficiency for the nonlinear crystal. Different cases were studied that simulate the effects of group velocity mismatch, phase mismatch, varying chirp and delay values, and crystal lengths. Results show that chirping the input pulses narrows the THz bandwidth while increasing its temporal duration, consistent with Fourier principles. The model also demonstrates the sensitivity of THz generation efficiency to phase-matching and crystal length. The thesis work contributes a simple yet robust computational tool for predicting THz generation performance under different input conditions and highlights practical limitations imposed by crystal length, phase mismatch and group velocity mismatch. The insights gained through simulations can help guide the design of efficient THz setups for future research studies/projects.
Keywords: THz generation; signal and idler; OPA; optical rectification; difference-frequency generation; chirp delay scheme; DSTMS; narrowband THz; Symmetric Split-Step Fourier Method; Runge-Kutta4